Reactivity of Small Molecular Forms of Human Factor VIII/von Willebrand Factor with Botrocetin and Anti-Factor VIII-Coated Latex Particles - Furlan, M; Perret, B A; Beck, E A (Thrombosis and Haemostasis, 1985)
Two recently developed tests for measurement of factor VIII/von Willebrand factor (FVIII/vWF), i.e. platetelet agglutination by botrocetin and a kinetic latex antigen assay, were compared with ristocetin cofactor and electroimmunoassay, in respect with FVIII/vWF size-distribution. FVIII/vWF was measured in six cases of atypical von Willebrand’s disease (type II), in gel-filtered fractions of normal cryoprecipitate and in the course of depolymerization of purified normal FVIII/vWF by disulfide reduction. Small molecular forms of FVIII/vWF from normal and variant type II plasma, and those derived by disulfide reduction of high-molecular weight FVIII/vWF, showed remarkably decreased reactivity in ristocetin-, botrocetin- and latex-assay. We conclude that for botrocetin-induced platelet agglutination, as well as for agglutination of antibody-coated latex particles, multiple interactions with repeating subunits of FVIII/vWF are required. As a practical consequence, the combined measurement of FVIII/vWF by the latex test and electroimmunoassay provides a simple tool for discriminating between the classical von Willebrand’s disease and its variants.
Keywords: Factor VIII/von Willebrand factor; Botrocetin; Antibody-coated latex particles